Penicillium on the Iris! An Unusual Presentation and Cause of Postoperative Anterior Uveitis - Jojo, Vijaya (Cureus, 2019)
Intraocular fungal infections may not present solely as postoperative anterior uveitis or as a focal anterior segment lesion. The present study describes a 50-year-old woman with well-controlled diabetes who presented with postoperative anterior uveitis three months after uncomplicated cataract surgery. A fuzzy lesion was observed on her iris. The patient underwent an anterior chamber wash and removal of the lesion, followed by intracameral treatment with voriconazole. Culture of the lesion showed that it was a species of Penicillium. The patient has remained stable after treatment. Three aspects of this case were unusual: a fungal lesion of unusual etiology and location, inflammation restricted to the anterior segment despite a fungal background, and the excellent response to treatment with a very favorable outcome.